Magnetic field effects on melting and solidification of PCMs in an isosceles triangular cavity - Haddad, Zoubida; Iachachene, Farida; Zidouni, Faiza; Öztop, Hakan Fehmi (Springer, 2022)
In the present study, the effects of a magnetic field on melting and solidification processes in an isosceles triangular cavity are numerically investigated, using a finite volume method along with an enthalpy-porosity technique. The magnetic field effects (magnitude and direction) on streamlines, isotherms, liquid fraction, and heat transfer are analyzed for Ra = 10(6) and a wide range of Hartmann number (0 <= Ha <= 100). As main outcomes, it is observed that contrary to the general trend, the strongest fluid flow stabilization is obtained when the magnetic field is directed parallel to the heated wall. When the magnetic field is horizontally and vertically oriented, the complete melting time is increased by 32.5% and 5.5%, respectively. It is found that the influence of the magnetic field is prominent and reaches a maximum value only during an intermediate stage of melting. Moreover, it is observed that the solidification process is not dependent on the magnetic field direction and magnitude. The complete time of melting at Ha = 100 is almost equal to the time of complete solidification.
Keywords: Melting; Solidification; Heat transfer; Natural convection; Magnetic field; Phase change material